Akuntansi Forensik Dalam Mendeteksi Kecurangan Pengadaan Barang dan Jasa di Sektor Pemerintah: Systematic Literature Review - Amelia Noor Anggraeni; Sri Mulyani (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to analyze the influence of forensic accounting, inhibiting factors and strategies to strengthen the application of forensic accounting in detecting fraud in the procurement of goods and services in the government sector. Method: The method taken is qualitative with a Systematic Literature review (LSR) approach. The data source used is secondary data taken from national and international article journals indexed by Google scholar in the period 2024 to 2026. The literature analyzed is mainly a research conducted on public organizations in Indonesia, and is focused on exploring the influence of forensic accounting on fraudulent procurement of goods and services. This research focuses on 8 journals that discuss how influential forensic accounting is, and the extent of the effectiveness of the application of forensic accounting on fraud in the procurement of goods and services.  Finding: The results of the study indicate that the application of forensic accounting plays an important role in increasing the effectiveness of fraud detection, especially in identifying manipulation of financial statements, administrative irregularities, and signs of corruption in the procurement process of goods and services. In addition, thorough audits and the expertise of forensic auditors also play a role in the successful identification of fraud. However, the determination of forensic accounting still experiences various challenges, such as a lack of human resources, a lack of supporting technology, and a weak internal control system. Therefore, it is necessary to improve the competence of auditors, the use of digital technology, and improve the supervision system to reduce the possibility of fraud in the public sector.